Changes in the hyoid bone, tongue, and oropharyngeal airway space after mandibular setback surgery evaluated by cone-beam computed tomography - Seon-Hye Kim; Sung-Kwon Choi (SpringerOpen, 2020)
Abstract Background Mandibular setback surgery can change the position of the mandible which improves occlusion and facial profile. Surgical movement of the mandible affects the base of the tongue, hyoid bone, and associated tissues, resulting in changes in the pharyngeal airway space. The aim of this study was to analyze the 3-dimensional (3D) changes in the hyoid bone and tongue positions and oropharyngeal airway space after mandibular setback surgery. Methods A total of 30 pairs of cone-beam computed tomography (CBCT) images taken before and 1 month after surgery were analyzed by measuring changes in the hyoid bone and tongue positions and oropharyngeal airway space. The CBCT images were reoriented using InVivo 5.3 software (Anatomage, San Jose, USA) and landmarks were assigned to establish coordinates in a three-dimensional plane. The mean age of the patients was 21.7 years and the mean amount of mandibular setback was 5.94 mm measured from the B-point. Results The hyoid bone showed significant posterior and inferior displacement (P < 0.001, P < 0.001, respectively). Significant superior and posterior movements of the tongue were observed (P < 0.05, P < 0.05, respectively). Regarding the velopharyngeal and glossopharyngeal spaces, there were significant reductions in the volume and minimal cross-sectional area (P < 0.001). The anteroposterior and transverse widths of the minimal cross-sectional area were decreased (P < 0.001, P < 0.001, respectively). In addition, the amount of mandibular setback positively correlated with the amount of posterior and inferior movement of the hyoid bone (P < 0.05, P < 0.05, respectively). Conclusion There were significant changes in the hyoid bone, tongue, and airway space after mandibular setback surgery.